2013
DOI: 10.4238/2013.february.27.4
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variability for root/shoot parameters under water stress in some advanced lines of cotton (Gossypium hirsutum L.)

Abstract: ABSTRACT. Research pertaining to genetic variability parameters, heritability, and genotypic, phenotypic, simple, and environmental correlations for various seedling traits in five elite advanced cotton (Gossypium hirsutum L.) lines (FH-113, FH-114, FH-941, FH-942, and FH-2015) and one check (CIM-496) was carried out during October and November 2010 under greenhouse conditions at the Cotton Research Institute (Faisalabad, Pakistan). Material was raised in plastic tubes with a randomized complete block design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 21 publications
6
47
0
Order By: Relevance
“…These differences may be due to the genetic make-up of collected Sesbania accessions (Joshi-Saha and Gopalakrishna, 2007; Sarwar et al, 2015). Riaz et al (2013) observed similar result in cotton germplasms and found significant variability among genotypes. Accession #26, 45, 47, 93, 97, 98, 101, 102, 116 120, 121 and 122 were performed better in terms of seedling vigour index (above 1440) (data not shown here).…”
supporting
confidence: 64%
“…These differences may be due to the genetic make-up of collected Sesbania accessions (Joshi-Saha and Gopalakrishna, 2007; Sarwar et al, 2015). Riaz et al (2013) observed similar result in cotton germplasms and found significant variability among genotypes. Accession #26, 45, 47, 93, 97, 98, 101, 102, 116 120, 121 and 122 were performed better in terms of seedling vigour index (above 1440) (data not shown here).…”
supporting
confidence: 64%
“…As reported earlier by MacCaughey (1917), G. tomentosum has xerophytic features such as deep root penetration and it is endemic to the dry coastal regions of Hawaii. The importance of root length for drought tolerance in cotton has previously been established (Riaz et al, 2013). Therefore, further research should focus on examining the root growth parameters of cotton under drought conditions and compare them with those of upland cultivated cotton.…”
Section: Discussionmentioning
confidence: 99%
“…The final linkage map consisted of 1295 markers that amplified 1342 loci (Tables S1 and S2). A complete cotton chromosome assignment for this map was done based on the previously chromosome-anchored map (Riaz et al, 2013).…”
Section: Linkage Mapmentioning
confidence: 99%
“…Ali et al (2008) studied the fiber quality in G. hirsutum L. and reported that the additive variance would be significant for all evaluated traits and relatively less than the dominance for length, resistance, fineness, uniformity, and elongation. Riaz et al (2013) conducted studies on various features of the five elite cotton lines of G. hirsutum. They recorded considerable genotypic variation among the genotypes and heritability estimates in the broad sense for all evaluated traits.…”
Section: Resultsmentioning
confidence: 99%